Mechanochemical Synthesis of Short DNA Fragments. Issue 41 (3rd July 2020) - Thorpe, James D.; O'Reilly, Daniel; Friščić, Tomislav; Damha, Masad J.
Abstract: We demonstrate the first mechanochemical synthesis of DNA fragments by ball milling, enabling the synthesis of oligomers of controllable sequence and length using multi‐step, one‐pot reactions, without bulk solvent or the need to isolate intermediates. Mechanochemistry allowed for coupling of phosphoramidite monomers to the 5′‐hydroxyl group of nucleosides, iodine/water oxidation of the resulting phosphite triester linkage, and removal of the 5′‐dimethoxytrityl (DMTr) protecting group in situ in good yields (up to 60 % over three steps) to produce DNA dimers in a one‐pot manner. H ‐Phosphonate chemistry under milling conditions enabled coupling and protection of the H ‐phosphonate linkage, as well as removal of the 5′‐DMTr protecting group in situ, enabling a one‐pot process with good yields (up to 65 % over three steps, or ca. 87 % per step). Sulfurization of the internucleotide linkage was possible using elemental sulfur (S8) or sulfur transfer reagents, yielding the target DNA phosphorothioate dimers in good yield (up to 80 % over two steps). This work opens the door to creation of solvent‐free synthesis methodologies for DNA and RNA therapeutics. Abstract : Shake to make DNA ! Utilizing mechanochemistry to make DNA fragments using both phosphoramidite and H ‐phosphonate chemistries under minimal solvent conditions (see figure).